Perancangan Perpustakaan Umum Daerah di Kota Gorontalo dengan Konsep Arsitektur Modern - Siti Nurullah B. Sue; Beby Sintia Dewi Banteng; Frans Mitran Ajami (Politeknik Kebangsaan, 2025)
This study addresses the lack of a representative and modern public library facility in Gorontalo City, which is a strategic center for education, trade, and services. Despite its potential, the city's current public library is not widely known due to its non-strategic location, resulting in low public engagement. Therefore, there is a need for a new public library that is not only functional and easily accessible but also equipped with modern technology and a captivating design to attract more visitors. The research focuses on the planning and design of a public regional library using a Modern Architectural Concept. This concept is applied to create a building that is highly functional, aesthetically pleasing, and adaptable to the dynamic needs of an urban community. The design incorporates various supporting facilities, such as an outdoor reading garden, discussion rooms, and accessibility features for people with disabilities. An efficient circulation and utility system is also integrated to enhance comfort, safety, and overall appeal. The findings from the planning and analysis indicate that this design contributes significantly to improving the quality of literacy in the community. Furthermore, the project has the potential to become a new landmark for Gorontalo City, serving as a representative educational facility and public space. This research demonstrates how modern architectural principles can be used to create an attractive, accessible, and beneficial public institution that meets the community's needs and fosters a culture of reading and learning.